Comparison of hematological and biochemical profile between Podolian grey steppe and Holstein cows - MLADENOVIC, V.; MARIC, M.; KÖNYVES, T.; STOJSIN, M.; ĐORDEVIC, S.; PUVACA, N.; HALÁSZ, A.; PAPADOPOULOS, E. (Journal of the Hellenic Veterinary Medical Society, 2021)
This research aimed to investigate the influence of different age of Podolian grey steppe and Holstein Friesian cows, as well as the effects of different breeds on their hematological and biochemical blood profile. A total of 128 adult cows aged from 3 to 12 years were used in the study. Gained results show statistically significant differences (P < 0.05) regarding all hematological parameters. The concentration of NE was recorded in the optimal range for Podolian grey steppe cows, while for Holstein Friesian breed was elevated.Values for LY was in the optimal range, while the values for MO, EO, and BA were slightly higher for both breeds of cow in all groups, with recorded significant differences (P < 0.05).Count of RBC in the Podolian grey steppe breed ranged between 5.83 and 11.21×1012/L, with significant influence (P < 0.05) of cows age in obtained values. In contrast, Holstein Friesian cows breed recorded RBC values lover then optimal, without any significant difference (P > 0.05) related to the age of cows. Total protein has ranged between 7.10 and 8.50 g/dl (Podolian grey steppe), and 8.13 to 8.48 g/dl (Holstein Friesian), without recorded statistically significant differences (P > 0.05) between the age, breed as well as the interaction of age and breed. Asimilar tendency can be seen regarding the otherbiochemical values (P>0.05), respectively.Gain results have mainly shown a significant influence of breed on the parameters above, while the significant influence of age of cows was not present as well the interaction between age and breed.